The abuse of BB1M (1Malaysia Book Voucher): integrity and time of distribution / Suriyati Ujang ...[et al.] - Ujang, Suriyati; Md Shah, Nursyaidatul Kamar; Khairol, Muhammad Hasrol Eizlan; Nor Azlan, Amir (2016)
The 1 Malaysia Book Voucher or Baucar Buku IMalaysia (BB1M), was introduced by the Malaysian government in 2012. The main objective of this initiative is to help ease financial burdens faced by students in higher education institution while purchasing educational books. However, cases have been reported that students were selling their BB1M worth RM250 at prices ranging from RM190 to RM230. Indirectly, this illustrates that the reading culture among Malaysians is still at a low level. This correlation study was conducted to find the relationship of the misused of the BB1M and the factor contributing to the abuse of BB1M. The objectives are to check whether student's integrity, gender, BB1M distribution time, student's appreciation and student's living cost can positively or negatively affect the abuse of BB1M. A set of questionnaires was distributed among 300 students Universiti Teknologi MARA, Raub Campus and descriptive statistics and inferential statistics were used in this research to find the result. The data analysis of this research revealed that there is no significant relationship between student's integrity and the abuse of BB1M; between BB1M distribution time and the abuse of the BB1M. However, the result suggested a significant relationship between students' living cost and the abuse of the BB1M and there is a significant relationship between gender and the abuse of the BB1M. Lastly, there is a significant relationship between student's appreciation and the misused of the BB1M. In a nutshell, student's living cost, gender and student's appreciation influence the abuse of the BB1M.